1968
DOI: 10.1002/cpt196894448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5‐imino‐2,2,4,4‐tetrakis (trifluoromethyn imidazolidine (EXP 338) on spasticity: A quantitative evaluation

Abstract: In preclinical studies, 5-imino-2,2,4,4-tetrakis (trifluoromethyl) Departments of Neurological Research, Neuropsychiatric Examining Service, and Therapeutics, Veterans Adminiotration Outpatient ClinicThe structure of 5-imino-2,2.,4,4-tetrakis (triRuoromethyl) imidazolidine (EXP 338)" is shown in Fig. l,1 Preclinical studies revealed that this preparation is capable of reducing abnormal neural activity by its effect on polysynaptic reRex arcs and to a lesser degree upon monosynaptic circuits in experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It was reported that the compound synthesized and its structure was elucidated by Middleton and Krespan in 1970, has apparent pharmacological activity as a muscle relaxant and central nervous system depressant as a result of clinical studies [10]. There are several studies about crystal structure analysis, pharmacological and toxicological effects of midaflur [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the compound synthesized and its structure was elucidated by Middleton and Krespan in 1970, has apparent pharmacological activity as a muscle relaxant and central nervous system depressant as a result of clinical studies [10]. There are several studies about crystal structure analysis, pharmacological and toxicological effects of midaflur [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%